The Homeless People in China During the COVID-19 Pandemic: Victims of the Strict Pandemic Control Measures of the Government - Wang, Ying; Hua, Lei; Zou, Shuyun; Deng, Taofeng; Chen, Yongqi; Cao, Wanying; Wu, Chuhan; Zhou, Yujie; Zou, Hua (Frontiers in Public Health, 2021)
Background: By implementing aggressive control measures, China has rapidly and effectively controlled the COVID-19 pandemic. However, the neglected homeless population may become victims of that perceived success. Due to political sensitivity, we know little about them. Aims: This study aimed to investigate how the pandemic and the government’s pandemic control strategies affected the lives of the homeless people in mainland China. Methods: 103 eligible participants experiencing absolute homelessness were recruited from Guangzhou City during July and August 2020. Surveys measured demographic characteristics including health status, changes in daily living, and the government’s actions toward the homeless during the pandemic. Sankey diagrams and ordered logit regression models were used to examine the impact on the homeless of inhumane government efforts to drive the homeless away. Qualitative materials were analyzed by using an inductive approach to provide more details. Results: First, the homeless people in Guangzhou tended to be male, aged 40 to 64 years, less well-educated, and they originated from outside Guangdong although they were living in the city center. Most had little connection with their families. After a long period of homelessness, almost half of the participants were in poor health with various conditions, which made them extremely vulnerable to COVID-19. Second, the pandemic caused a substantial decline in homeless people’s incomes, had less of a negative impact on their food intake, and affected sleep time in different ways. Third, during the COVID-19 pandemic, humanitarian aid from China’s local governments decreased, whereas inhumane efforts to drive the homeless away intensified. Fourth, quantitative models and qualitative materials demonstrate the devastating effect of the government’s strict pandemic control strategy on homeless people’s lives, which may further cause their health problems. Conclusion: This study for the first time illustrated the characteristic features of the street homeless population in mainland China and their living situation during the COVID-19 pandemic, and most importantly demonstrated the devastating effect of governments’ strict pandemic control, which has been considered a great success in previous studies, on homeless people’s lives. Urgent measures should be taken to ensure the protection of the homeless population and prevent any impending humanitarian crisis.